Biapenem in binary aqueous mixtures of N, N-dimethylformamide, N-methyl-2-pyrrolidone, isopropanol and ethanol: Solute-solvent and solvent-solvent interactions, solubility determination and preferential solvation. (October 2020) - Zhu, Changfei; Xu, Renjie; Zhou, Yanyan; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of biapenem in four aqueous mixtures was determined and correlated. Preferential solvation of biapenem were derived via IKBIs method applied to solubility. Solvent effect on solubility variation was investigated through KAT-LSER model. Abstract: This work mainly aimed to study the mole fraction solubility of biapenem in four binary solutions of N, N -dimethylformamide (DMF, 1) + water (2), isopropanol (1) + water (2), N-methyl-2-pyrrolidone (NMP, 1) + water (2) and ethanol (1) + water (2). Experiments were performed through a common static equilibrium method at temperatures from 283.15 to 323.15 K. The maximum solubility magnitudes were observed in pure solvent of DMF/NMP/isopropanol/ethanol for each solution. The achieved biapenem solubility was mathematically described by using two famous co-solvency models, Jouyban-Acree and van't Hoff-Jouyban-Acree. The calculated relative average deviations were not greater than 4.20%; and root-mean-square deviations, not greater than 7.45 × 10 −6 . The linear solvation energy relationships method put forward by Kamlet and Taft was employed to examine the influence of solvent descriptors upon biapenem solubility behaviour. The principal contributors to solvent effect was hydrogen bond acidity for DMF/NMP mixtures; and hydrogen bond acidity and non-specific dipolarity-polarizability for isopropanol/ethanol mixtures. Quantitative local mole fractions of DMF (NMP, isopropanol or ethanol) and water nearby the biapenem were analyzed through Inverse Kirkwood–Buff integrals method. For the isopropanol/ethanol + water mixtures within water-rich compositions, biapenem was preferentially solvated by isopropanol/ethanol; while within intermediate and co-solvent-rich compositions, by water. However, for the DMF/NMP mixture within entire composition ranges, the absolute δx 1, 3 values were all smaller than 1.0 × 10 −2, consequently biapenem was not preferentially solvated by DMF/NMP or water.